2009
DOI: 10.1038/ismej.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

Predators promote defence of rhizosphere bacterial populations by selective feeding on non-toxic cheaters

Abstract: Soil pseudomonads increase their competitiveness by producing toxic secondary metabolites, which inhibit competitors and repel predators. Toxin production is regulated by cell-cell signalling and efficiently protects the bacterial population. However, cell communication is unstable, and natural populations often contain signal blind mutants displaying an altered phenotype defective in exoproduct synthesis. Such mutants are weak competitors, and we hypothesized that their fitness depends on natural communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 46 publications
7
143
3
Order By: Relevance
“…This mutant is typical for spontaneous mutations deactivating secondary metabolism in pseudomonads 28 and lacks extracellular proteases required for growing on albumin 3,30 . It grows better than the wild type when cooperation is not required 4 , but preliminary experiments showed that it is incapable of growing on QSM medium alone. In order to investigate its growth inhibition by the cooperators, we grow this mutant under nonlimiting nutrient conditions (Lysogeny Broth (LB)) supplemented with small amounts of supernatant from communities grown in QSM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mutant is typical for spontaneous mutations deactivating secondary metabolism in pseudomonads 28 and lacks extracellular proteases required for growing on albumin 3,30 . It grows better than the wild type when cooperation is not required 4 , but preliminary experiments showed that it is incapable of growing on QSM medium alone. In order to investigate its growth inhibition by the cooperators, we grow this mutant under nonlimiting nutrient conditions (Lysogeny Broth (LB)) supplemented with small amounts of supernatant from communities grown in QSM.…”
Section: Resultsmentioning
confidence: 99%
“…Invasion by unrelated defectors occurs from outside the population, whereas signal-blind defector mutants emerge by cell division inside the population of the cooperating ancestor. Based on our results, we propose that inhibition of closely related defectors was due to a combination of policing, in which cooperators invest into harming of defectors 34 , and disruption of QS via pleiotropic effect reducing resistance to various biotic and abiotic stressors 4,35 . The increased sensitivity of defectors to genetically related cooperators points to a suppression of close kin refusing to cooperate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such costs may differ between individuals adopting different social behaviours, and include energy or time committed to defence or resistance (e.g. [22,24]), or costs associated with trade-offs involved in evolved resistance to enemies [19,20]. Despite their ubiquitousness in nature and demonstrated importance in population ecology and evolutionary biology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[16,19,20], but see [21]), or constitute a cost that potentially impacts other cooperative behaviours (e.g. resource access and sharing, quorum sensing [19,22,23]). Such costs may differ between individuals adopting different social behaviours, and include energy or time committed to defence or resistance (e.g.…”
Section: Introductionmentioning
confidence: 99%